Current and Emerging Technologies for the Diagnosis of Microbial Infections - Sails, Andrew; Tang, Yi-Wei (Academic Press, 2015)
In this book the latest volume of series, provides comprehensive, cutting-edge reviews of current and emerging technologies in the field of clinical microbiology. The book features a wide variety of state-of-the art methods and techniques for the diagnosis and management of microbial infections, with chapters authored by internationally renowned experts. This volume focuses on current techniques, such as MALDI-TOF mass spectroscopy and molecular diagnostics, along with newly emerging technologies such as host-based diagnostics and next generation sequencing. -- Provided by publisher.
Keywords: Communicable diseases -- Diagnosis.; Communicable diseases -- Diagnosis -- Technological innovations.; elektronické knihy; electronic books